2020
DOI: 10.1002/asl.1018
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological impacts of a novel debris‐covered glacier category in a regional climate model across a Himalayan catchment

Abstract: Many of the glaciers in the Nepalese Himalaya are partially covered in a layer of loose rock known as debris cover. In the Dudh Koshi River Basin, Nepal, approximately 25% of glaciers are debris‐covered. Debris‐covered glaciers have been shown to have a substantial impact on near‐surface meteorological variables and the surface energy balance, in comparison to clean‐ice glaciers. The Weather Research and Forecasting (WRF) model is often used for high‐resolution weather and climate modelling, however representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…Overall, the model manages to simulate the diurnal cycle of the winds that was evident in the observations. The along-valley wind characteristics in Khumbu Valley were found to be similar to what previous research has shown, with respect to both observational (Inoue, 1976;Ueno and Kayastha, 2001;Bollasina et al, 2002;Ueno et al, 2008;Bonasoni et al, 2010;Shea et al, 2015) and model-based studies (Potter et al, 2018(Potter et al, , 2021.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Overall, the model manages to simulate the diurnal cycle of the winds that was evident in the observations. The along-valley wind characteristics in Khumbu Valley were found to be similar to what previous research has shown, with respect to both observational (Inoue, 1976;Ueno and Kayastha, 2001;Bollasina et al, 2002;Ueno et al, 2008;Bonasoni et al, 2010;Shea et al, 2015) and model-based studies (Potter et al, 2018(Potter et al, , 2021.…”
Section: Discussionsupporting
confidence: 87%
“…This study concentrates on four valleys located in the Nepal Himalayas during a 4 d period in December 2014. The local wind patterns in Khumbu Valley (one of the valleys that is investigated in this study) have been studied in the past by means of meteorological observations (Inoue, 1976;Ueno and Kayastha, 2001;Bollasina et al, 2002;Ueno et al, 2008;Bonasoni et al, 2010;Shea et al, 2015;Yang et al, 2018) and high-resolution meteorological modelling (Karki et al, 2017;Potter et al, 2018Potter et al, , 2021. Overall, the daily cycle of the along-valley winds in Khumbu Valley are simi-lar among existing studies, with well-defined daytime upvalley winds and weaker night-time winds flowing either in the up-or down-valley direction.…”
Section: Introductionmentioning
confidence: 99%
“…Spatially distributed wind modeling is more challenging and involves complex relationships with respect to topography and thermal/dynamic atmospheric processes (Ayala et al, 2017;Potter et al, 2020). In this study, the wind pattern is spatialized using equations from the MicroMet model (Liston & Elder, 2006;Liston & Sturm, 1998):…”
Section: Spatialization Of Meteorological Datamentioning
confidence: 99%
“…Spatially distributed wind modeling is more challenging and involves complex relationships with respect to topography and thermal/dynamic atmospheric processes (Ayala et al., 2017; Potter et al., 2020). In this study, the wind pattern is spatialized using equations from the MicroMet model (Liston & Elder, 2006; Liston & Sturm, 1998): u=uAWS1+γsnormalΩs+γcnormalΩc1+γsnormalΩs(AWS)+γcnormalΩc(AWS) $u={u}_{AWS}\ast \frac{\left(1+{\gamma }_{s}{{\Omega }}_{s}+{\gamma }_{c}{{\Omega }}_{c}\right)}{\left(1+{\gamma }_{s}{{\Omega }}_{s(AWS)}+{\gamma }_{c}{{\Omega }}_{c(AWS)}\right)}$ where u is the topographically modified wind speed, u AWS is the measured wind speed at the AWS site, Ω c the terrain curvature, and Ω s is the slope in the direction of the wind: Ωs=St()θuAt ${{\Omega }}_{s}={S}_{t}\left({\theta }_{u}-{A}_{t}\right)$ …”
Section: Location Data and Modelsmentioning
confidence: 99%
“…Studies employing distributed energy balance models could, for example, test the melt-equalizing effect of debris at the glacier scale and its overall effect on the catchment runoff. This could be combined with generating spatially consistent forcing data using high-resolution weather modelling as in Bonekamp et al (2019) or Potter et al (2020), and expanded to larger domains. Realistic representations of the glacier surface, including distributed debris thickness, and supraglacial features, such as ice cliffs and surface ponds, should also be established to provide well-constrained water budgets and improved representations of glacierised environments in land-surface models under present and future environmental conditions.…”
Section: Future Workmentioning
confidence: 99%